2018
DOI: 10.1016/j.radcr.2018.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumor of the ischioanal fossa—a multidisciplinary approach to management with radiologic-pathologic correlation

Abstract: Solitary fibrous tumors are primary mesenchymal tumors, which may occur in any part of the body. Overall, these tumors are considered to have intermediate malignant potential with 5- and 10-year metastasis-free and overall disease-specific survival rates of 74% and 55%, and 89% and 73%, respectively (Demicco et al, 2012). Herein we present an unusual case of solitary fibrous tumors involving the ischioanal fossa in a 19-year-old woman with radiologic-pathologic correlation. This case was complicated by extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In our review, only 2 out of the 13 cases (including ours) had a preoperative biopsy. From these 2 cases, Bhat et al report that a CT-guided biopsy was performed; however, it was complicated with intralesional hemorrhage [ 16 ]. In the report by Morikawa et al, an ultrasound-guided biopsy was performed to assist with the management strategy, as the patient was reluctant to have an operation in case of a benign lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In our review, only 2 out of the 13 cases (including ours) had a preoperative biopsy. From these 2 cases, Bhat et al report that a CT-guided biopsy was performed; however, it was complicated with intralesional hemorrhage [ 16 ]. In the report by Morikawa et al, an ultrasound-guided biopsy was performed to assist with the management strategy, as the patient was reluctant to have an operation in case of a benign lesion.…”
Section: Discussionmentioning
confidence: 99%
“…[3,[6][7][8] e probability of malignancy within a SPN may be estimated using existing models. [9][10][11][12][13][14] Guidelines from the American College of Chest Physicians [1,15,16] recommend direct surgical approach or follow-up with serial CT scans, depending on the high or low malignant probability of the SPN, respectively. [9,17] However, in cases of a SPN with intermediate probability of malignancy or for patients with a high surgical risk, the recommendation is to biopsy the lesion, most often CT-guided.…”
Section: Introductionmentioning
confidence: 99%
“…Among the mortality of tumor-related diseases, the HCC mortality of males ranks second, and the HCC mortality of females ranks sixth ( 2 ). The pathological grading of HCC is an important predictor of the recurrence and survival of HCC patients after surgery or liver transplantation ( 6 , 7 ). The risk of recurrence and metastasis of patients with poorly-differentiated HCC is significantly higher than that of patients with moderately-differentiated HCC ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the incidence of HCC is affected by many risk factors ( 5 , 6 ). HCC mostly occurs on the basis of liver cirrhosis, and then undergoes several stages of transformation, from regenerative nodules to dysplasia to liver cancer, which is accompanied by tumor angioarchitecture and blood perfusion ( 7 , 8 ). Early detection and diagnosis of HCC lesions and recurrence are important for improving the long-term prognosis and quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%